Artemisia argyi extract ameliorates IL‐17A‐induced inflammatory response by regulation of NF‐κB and Nrf2 expression in HIG‐82 synoviocytes. Issue 11 (12th August 2022) - Chen, Jhong‐Kuei; Kuo, Chia‐Hua; Kuo, Wei‐Wen; Day, Cecilia Hsuan; Wang, Tso‐Fu; Ho, Tsung‐Jung; Lin, Pi‐Yu; Lin, Shinn‐Zong; Shih, Tzu‐Ching; Shih, Cheng‐Yen; Huang, Chih‐Yang; Lu, Cheng‐You
Abstract: Rheumatoid arthritis (RA) is an autoimmune and chronic inflammatory disease that results in joint destruction and disability in the adult population. RA is characterized by the accumulation and proliferation of fibroblast‐like synoviocytes. Many pro‐inflammatory mediators are associated with RA, such as interleukin (IL)‐1β, IL‐6, IL‐17, cyclooxygenase‐2 (COX‐2), and nuclear factor kappa B (NF‐κB). Furthermore, IL‐17 upregulates the production of other pro‐inflammatory mediators, including IL‐1β and IL‐6, and promotes the recruitment of neutrophils in RA. Artemisia argyi, a traditional Chinese herbal medicine, is used for the treatment of diseases associated with inflammation and microbial infections. In this study, synoviocytes (HIG‐82) were treated with varying doses of A. argyi extract (AAE) following IL‐17A stimulation. Proliferation of the IL‐17A‐stimulated cells was increased compared to that of the non‐stimulated control cells. However, cell proliferation decreased significantly in a dose‐dependent manner following AAE treatment. Treatment of IL‐17A‐stimulated cells with AAE resulted in decreased levels of phosphorylated (p)‐NF‐κB, p‐IκB‐α, and COX‐2. Enzyme‐linked immunosorbent assay results showed that IL‐1β and IL‐6 levels were increased in the IL‐17A‐stimulated group but decreased in the AAE treatment group. Additionally, we found that AAE facilitated nuclear factor erythroid 2‐related factor 2 (Nrf2) expression and promoted its nuclear translocation, thereby inducing the expression of heme oxygenase‐1. Moreover, AAE did not attenuate IL‐17A‐induced inflammatory mediator production in the presence of ML385, an Nrf2‐specific inhibitor. These results suggest that the downregulation of expression of pro‐inflammatory cytokines and the transcription factor NF‐κB by AAE may be a potential therapeutic strategy for reducing inflammation associated with RA.